A GUERRA FLUVIAL: A ENGENHARIA INDÍGENA NO PROCESSO DE EXPANSÃO NEERLANDESA NO MARANHÃO E GRÃO-PARÁ (1621 - 1641). - SOUSA, Karolynne Soares (2019)
In the seventeenth century, the River War was the representation of how the Dutch expansion proceeded in the region of the former State of Maranhão and Grão-Pará, the theme to be analyzed in this study, from the construction of fortifications and how they were constituted by cooperation and indigenous engineering, the main actors in this narrative. Initially, it will be demonstrated how the Dutch Atlantic was constituted with the consolidation of the Iberian Union and the fragmentation of trade relations between the Spanish-Portuguese and the Low Countries, and consequently, the rebellion against Hispanic monarchy. Therefore, it will be studied how the experiences of wars that occurred in the State of Maranhão and Grão-Pará, different from those promoted in the State of Brazil, were fundamental for the establishment of the Dutch Amazon in the sixteenth century and how indigenous collaboration fostered trade and piracy by the Tupinambá routes. It will be evident at the end of the study, how the Dutch established and maintained their power relations in the Amazon Delta, against the backdrop of the fortifications built by the indigenous, essential actors. Thus, we also discuss the notion of New Military History, which was extremely important for the development of the work and better use of historical documentation. As for the basic theoretical references, we have documents such as the Overseas Archive, General Archive of Simancas, General Archive of Indies, Nationaal Archief (The Hague) and the sources of the National Library of Rio de Janeiro, as well as the letters, requirements and crafts that they were written between the Iberian kingdoms and the officers or travelers who were in the region in the 17th century, characterizing the historical method.